Report on IIUM event management checklist and KAED-ICT SOPs - Yaali, Syarel Azill; Ayob, Mohd Fairullazi (2017)
These report and Standard of Procedures (SOP) are prepared to provide guidelines and checklist that can facilitate departments and kulliyyah to disseminate news and information of the events and programmes.